Experimental evidence for the elusive ketohydroperoxide pathway and the formation of glyoxal in ethylene ozonolysis. Issue 94 (9th November 2022) - Lewin, Caroline Smith; Herbinet, Olivier; Garcia, Gustavo A.; Arnoux, Philippe; Tran, Luc-Sy; Vanhove, Guillaume; Nahon, Laurent; Battin-Leclerc, Frédérique; Bourgalais, Jérémy
Abstract : Despite decades of research, an unambiguous kinetic network in ethylene ozonolysis remain elusive. This experimental work demonstrates that a substantial fraction of the primary ozonide leads to 2-hydroperoxyacetaldehyde which decomposes to glyoxal. Abstract : Despite decades of research on alkene ozonolysis, the kinetic network of the archetypal case of ethylene (CH2 CH2 ) with ozone (O3 ) still lacks consensus. In this work, experimental evidence of an elusive diradical pathway is provided through the detection of the 2-hydroperoxyacetaldehyde ketohydroperoxide and its decomposition product, glyoxal.